2012
DOI: 10.7783/kjmcs.2012.20.3.177
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Growth Characteristics and Ginsenosides Content of 6-Year-Old Ginseng (Panax ginseng C. A. Meyer) by Drainage Class in Paddy Field

Abstract: : To develop the practical cultivation for paddy field, we investigated the properties of paddy soil, growth characteristics and ginsenoside content of 6-year-old ginseng, Cheonpung variety between poor drainage class (PDC) and imperfect drainage class (IDC). Groundwater level in PDC showed monthly small changes of 20~30 ㎝, while IDC showed monthly great changes of 28~71 ㎝ depending on rainfall. Soil moisture content in PDC and IDC was 17.2%, 22.5%, respectively. Air temperature in IDC was lower than 0.3℃, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 2 publications
0
4
0
6
Order By: Relevance
“…However, Li (1997) also reported that roots were shorter in loamy sand than in sandy loam soils despite the higher sand content and suggested that the effect of soil particle size could be confounded by other factors. It is likely that soil with a small particle size has more moisture (Saxton and Rawls, 2006); therefore, poor drainage may decrease root weight (Lee et al, 2012). High soil moisture suppresses ginsenoside production in P. ginseng (Lee et al, 2012).…”
Section: Effects Of Soil Texture On Root Growth and Ginsenoside Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Li (1997) also reported that roots were shorter in loamy sand than in sandy loam soils despite the higher sand content and suggested that the effect of soil particle size could be confounded by other factors. It is likely that soil with a small particle size has more moisture (Saxton and Rawls, 2006); therefore, poor drainage may decrease root weight (Lee et al, 2012). High soil moisture suppresses ginsenoside production in P. ginseng (Lee et al, 2012).…”
Section: Effects Of Soil Texture On Root Growth and Ginsenoside Contentmentioning
confidence: 99%
“…There has been growing interest in developing cultural methods to control both root mass yield and ginsenoside content (Park et al, 1986;Lee et al, 2012). However, there is little information on the effects of soil quality and climate on the cultivation of P. ginseng.…”
Section: Introductionmentioning
confidence: 99%
“…그러나 논토양에서 인삼을 재배하면 지대가 낮은 곳에서는 배수불량으로 습해가 발생하기 쉽고 벼 재배시 담수와 배수의 반복으로 인해 용출된 철이 과잉 흡수되어 갈반형 황증이 생 기기 쉽다 (Lee et al, 2012(Lee et al, , 2013b. 인삼 잎에 나타나는 생리장해의 일종인 황증은 주로 황색 반점형, 갈색 반점형, 엽연형으로 구분되는데 (Hyun et al, 2009), 논재배에서는 주로 갈색 반점형 황증이 많이 발생한다 (Lee et al, 2013b).…”
Section: 서 언unclassified
“…가 많다 (Lee et al, 2012b). 논토양에서는 인삼 잎에 많이 발생하는 황증은 철분의 과잉 흡수로 인해 생기는 갈반형 황증이 대부분인데, 논토양에서는 밭토양보다 대부분 pH가 낮아 산화철 (Fe 3+ )의 용해도가 증가 되므로 토양용액 속에 가용성 철 함량이 높아진다 (Lee et al, 2012b).…”
unclassified
“…논토양에서는 인삼 잎에 많이 발생하는 황증은 철분의 과잉 흡수로 인해 생기는 갈반형 황증이 대부분인데, 논토양에서는 밭토양보다 대부분 pH가 낮아 산화철 (Fe 3+ )의 용해도가 증가 되므로 토양용액 속에 가용성 철 함량이 높아진다 (Lee et al, 2012b). 또한, 벼 재배시 담수와 배수불량은 토양환원을 촉진 시켜 토양용액 속에 환원철 (Fe…”
unclassified